"Netwar": The unwelcome militarization of the Internet has arrived. (3rd September 2017) - Zittrain, Jonathan
ABSTRACT: The architecture and offerings of the Internet developed without much steering by governments, much less operations by militaries. That made talk of "cyberwar" exaggerated, except in very limited instances. Today that is no longer true: States and their militaries see the value not only of controlling networks for surveillance or to deny access to adversaries, but also of subtle propaganda campaigns launched through a small number of wildly popular worldwide platforms such as Facebook and Twitter. This form of hybrid conflict – launched by states without state insignia, on privately built and publicly used services – offers a genuine challenge to those who steward the network and the private companies whose platforms are targeted. While interventions by one state may be tempered by defense by another state, there remain novel problems to solve when what users see and learn online is framed as organic and user-generated but in fact it is not.